Applying a developmental lens to examine injury mortality in young people in Australia, 2001‐2013. (18th November 2018) - Seah, Rebecca; Mitchell, Rebecca J.
Abstract: Issue addressed: As injuries are preventable, understanding the age profile of specific injury mechanisms is critical for developing injury prevention strategies. This study examined the profile and temporal trends of injury mortality of young people aged ≤24 years in Australia across developmental life stages. Method: A retrospective analysis of injury deaths of young people aged ≤24 years was conducted using closed cases from the National Coronial Information System during 2001‐2013. Negative binomial regression was used to examine temporal trends in mortality rates by age group. Results: There were 7749 injury deaths of young people in Australia. The mortality rates were estimated to decline each year for young people aged 0‐4 years (by 3.4%; 95% CI: −5.10 to −1.67), 10‐14 years (by 3.7%; 95% CI: −6.29 to −1.09), 15‐19 years (by 4.4%; 95% CI: −5.90 to −2.85) and 20‐24 years (by 4.5%; 95% CI: −5.61 to −3.37). Motor vehicle incidents were a frequent mechanism of fatal injury for all ages. For children aged ≤9 years, drowning and submersion and other threats to breathing were also frequent mechanisms of fatal injury. Young people aged 15‐24 years were also frequently fatally injured as a motorcyclist or a pedestrian. Conclusions: The age‐specific injury mortality profiles reflect the changing vulnerabilities of young people influenced by physical, cognitive and social characteristics associated with different stages of their development. By focusing on different ages, targeted injury prevention interventions can be developed. So what?: While policies play a key role in reducing injury mortality, secondary interventions that aim to shift attitudes to injury prevention activities will also be critical to influence positive behaviour change.